The right to decide: brief notes on its theoretical soundness and strategic convenience - Payero López, Lucía (EUNOMÍA. Revista en Cultura de la Legalidad, 2020)
Supporters of the right to decide insist on highlighting the differences between this right and national self-determination with the aim of avoiding criticism addressed to the latter. This article will argue that the right of self-determination presents a more solid theoretical basis than those versions of the right to decide that are intended to separate both concepts, even though this distinction can be interesting in terms of political strategy. Moreover, it will be pointed out that advocates of the right to decide sometimes characterise it with similar features to national self-determination, which blurs the lines between them.